Conceptual model of the concept of "Сhemical Reaction" - Shaposhnyk, A. M. (Problems of Engineer-Pedagogical Education, 2018)
In the article the prospects of the chemical industry and businesses. Despite the rather wide range of products, all of them can be summarized by the basic principle of chemical reactions and production technologies. Given the current trends in the industry identified the need for training of future specialists chemical profile and develop appropriate teaching methods. An analysis of studies devoted to the formation of chemical engineering concepts and identified the major problem. Established that the system of concepts of chemical technology creates optimal conditions for the development of thinking, logic thinking, the formation of a scientific outlook on things and phenomena linkages between them, disclosure laws chemical laws of many processes, phenomena and relations. Theoretically, the expediency of the model based on semantic features to establish the relationship between the characteristics of the chemical reaction. The conceptual model of the concept of "chemical reaction", which contains a hierarchical set of attributes that represent the purpose, structure, composition, construction, principles, mechanisms of action and operation parameters, characteristics and properties of the chemical reaction.